2011
DOI: 10.1080/08870446.2010.495157
|View full text |Cite
|
Sign up to set email alerts
|

Can the effectiveness of health promotion campaigns be improved using self-efficacy and self-affirmation interventions? An analysis of sun protection messages

Abstract: Health-risk communications frequently target self-efficacy in order to encourage adaptive responses. Research has also indicated that self-affirmation may be a useful supplementary or alternative intervention technique. This study compared the effects of self-efficacy, self-affirmation and a combination of these techniques for two risk messages. Young British females (N=677) read about ultraviolet light and skin cancer or skin ageing ('photoageing') and were randomly assigned to a single intervention (self-aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 46 publications
2
37
0
Order By: Relevance
“…One exception to this lack of variation was patients' reported perceived threat at baseline though the difference remained non-significant. Self-affirmed patients rated the health message to be more threatening than controls with small effect sizes observed (d=.21), consistent with previous research (Armitage et al, 2011;Good & Abraham, 2011). However the effect was lost when adjusted for clinical factors.…”
Section: Evaluation Of the Health Risk Informationsupporting
confidence: 80%
“…One exception to this lack of variation was patients' reported perceived threat at baseline though the difference remained non-significant. Self-affirmed patients rated the health message to be more threatening than controls with small effect sizes observed (d=.21), consistent with previous research (Armitage et al, 2011;Good & Abraham, 2011). However the effect was lost when adjusted for clinical factors.…”
Section: Evaluation Of the Health Risk Informationsupporting
confidence: 80%
“…However, one possibility for why Iowa students who had seen their UV photo showed more yellow saturation (i.e., more tan) at the post-summer follow-up is that they may have reacted to the photo with greater defensiveness. That is, recent work has shown that young adults may demonstrate greater defensiveness in response to appearance-based interventions (Good & Abraham, 2011), perhaps because the sun exposure-photoaging link has traditionally received less attention in the media and, therefore, seems less well established than the sun exposureskin cancer link. The generally colder and less sunny climate of Iowa relative to Southern California may mean even less local media attention devoted to sun exposure risks, thus making it easier for Iowa participants to deny or question appearance-based messages.…”
Section: Supplementary Materialsmentioning
confidence: 98%
“…Self-efficacy is related to performing sun protection behaviours [9,36,37,40,41]. Individuals have varying levels of self-efficacy about being able to do all the behaviours necessary to protect their skin [36].…”
Section: Self-efficacymentioning
confidence: 99%